تاريخ القراء في جبل نفوسة قراء نالوت أنموذج - المقدمي, نادية عيسى خليفة (المجلة الأفروآسيوية للبحث العلمي, 2025)
The research addresses the topic of Quran readers in Jabal Nafusa, particularly in the city of Nalut, shedding light on how the Quran was transmitted and preserved. It aims to answer questions regarding the first reader in the area, the methods of memorization used, and the most famous readers. Additionally, it seeks to clarify the role of Nafusa's readers in preserving the Quran and the reasons for its spread in the community. The research is structured into an introduction and two main sections, with the first focusing on the history of readers in Jabal Nafusa and the second on the history of readers in Nalut. The researcher employed a historical narrative approach and analysis to utilize various sources. It is hoped that this work will be a step toward documenting the history of the city's readers.
Keywords: Coran – apprentissage

طرق تحفيظ القرآن: آراء واقتراحات - أولاد سعيد, أحمد بن سعد (الأعمال الكاملة للآيام الدراسية العلمية: من الشيخ عمي سعيد بن علي الجري [ن 927 هـ/1521م] إلى الشيخ حمو بن موسي عمي سعيد [ت 1425 هـ/2005 م] مسيرة علمية تربوية اجتماعية ، عوية رائكة... ومتواصلة. أيام: 09-11 شوال 1427 ه / 01-03 نوفمبر 2006م مسجد بابا السعد الشرقي - غرداية, 2024)
Keywords: Coran – apprentissage

طرق تحفيظ القرآن: آراء واقتراحات - لعساكر, عمر بن قاسم (الأعمال الكاملة للآيام الدراسية العلمية: من الشيخ عمي سعيد بن علي الجري [ن 927 هـ/1521م] إلى الشيخ حمو بن موسي عمي سعيد [ت 1425 هـ/2005 م] مسيرة علمية تربوية اجتماعية ، عوية رائكة... ومتواصلة. أيام: 09-11 شوال 1427 ه / 01-03 نوفمبر 2006م مسجد بابا السعد الشرقي - غرداية, 2024)
Keywords: Coran – apprentissage